The best fuel selection with hybrid multiple-criteria decision making approaches in a CI engine fueled with their blends and pure biodiesels produced from different sources - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In engine tests where the feasibility of alternative fuels is being investigated, the results of the engine performance, combustion characteristics, and exhaust emissions should be considered as a whole. It is difficult to determine the optimal parameters due to a large number of results obtained in multi-variable experiments. Multi-criteria decision making (MCDM) methods are preferred in solving such problems to energy management and energy efficiency. This paper deals with an application of a novel hybrid MCDM technique is suggested to select the optimum fuel for the compression ignition (CI). Five academicians who are an expert in the field of CI engines are selected to set criteria in the MCDM. Engine tests carried out at the constant engine speed and the resistive load of 10.8 kW in the generator-engine set. The results were used in the MCDM process. In this study, the hybrid models which are SWARA-MOORA, and ANP-MOORA has been preferred as the MCDM methods. The best fuel choice was made from fuels such as animal fat biodiesel (AFB), vegetable oil biodiesel (VOB), diesel fuel and the blend fuels. According to results, it was determined that the best fuel is VOB20 in both hybrid methods according to the determined criteria. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Multi-criteria decision making (MCDM); Vegetable oil biodiesel (VOB); Animal fat biodiesel (AFB); ANP; SWARA; MOORA; Best fuel selection; ANALYTIC NETWORK PROCESS; DIESEL-ENGINE; FISH-OIL; COMBUSTION CHARACTERISTICS; ALTERNATIVE FUELS; EXHAUST EMISSIONS; PROCESS ANP; FUZZY AHP; PERFORMANCE; PARAMETERS